PERANAN BADAN USAHA MILIK DESA (BUMDES) SEBAGAI IMPLEMENTASI EKONOMI KREATIF DALAM RANGKA PEMBERDAYAAN MASYARAKAT DESA JALANCAGAK KECAMATAN JALANCAGAK KABUPATEN SUBANG PROVINSI JAWA BARAT - Romi Saputra (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2017)
Rule the Village And You Rule The Country, an adage that inspired the authors to examine the BUMDes Jalancagak. This study focuses the problem on: Role BUMDes Jalancagak in the implementation of the Creative Economy; Attempts were made BUMDes Jalancagak; Constraints BUMDes Running Jalancagak in business. The method used is a method descriptively by inductive approach the author in the sample using a sample set aims (purposive sampling). The data collection techniques through interviews, questionnaires and documentation. Based on the analysis we concluded that BUMDes Jalancagak has been cast as the implementation of the creative economy in order to empower villagers Jalancagak accordance with Regulation Subang District No. 14 Year 2007 on Guidelines for the Establishment BUMDes. Credit management BUMDes Jalancagak use banking management, especially rural banks and credit is the most desirable BUMDes business community. Low BUMDes human resource officer is the main limiting factor BUMDes in business management. The authors suggest that the role of BUMDes Jalancagak as the implementation Creative Economy village-owned Jalancagak maintained and further improved, because of the benefits BUMDes has been strengthening revenue village, so the village Jalancagak able to independently finance the activities of the village in order to realize the improvement of living standards and maintain preservation of customs and culture of the people in order to empower villagers Jalancagak. Keywords: implementation, creative economy, empowerment